On Extended Context Free Grammars and LR-Parsing - Madsen, Ole Lehrmann; Kristensen, Bent Bruun (DAIMI Report Series, 1975)
A dynamically microprogrammable processor called MATHILDA is described.MATHILDA has been designed to be used as a tool in interpreter and processor design research. It has a very general microinstruction sequencing scheme, sophisticated masking and shifting capability, high speed local storage, a 64-bit wide main data path, a partially encoded microinstruction, and other features which make it reasonably well suited for this purpose. Also, hardware modification is relatively easily undertaken to enhance the experimental nature of the machine. Revised version (first version 1975).